A STUDY ON IMPACT OF FINANCIAL LITERACY ON WOMEN IN BENGALURU CITY - Dr. S.Ramesh,; S, Dr. Umamaheswari. (The journal of contemporary issues in business and government, 2021)
The growth and development of a place or people all are based on their financial condition. Finance is playing a key role for measuring the living standards of people and evaluate the economic growth of a country. Therefore, the people should have knowledge of various sources of finance investment and its importance. The purpose of this research work is to study the financial literacy of working women respondents and their preferable source of investments on financial products. In this study, financial literacy mentioned as knowledge of various investment sources of finance like bank savings, post office savings, Investment on mutual fund, capital market and gold. Hence, the study was collected information through questionnaire from different category of working women respondents. The data was collected from respondents with the questions entailing with their knowledge of various sources of financial investment and its avenues. The research study used the basic descriptive statistics and One-way ANOVA to test the hypothesis. The study found that most of the women are good in savings & borrowings, Loan issues but they have less experience in handling investment issues, calculation of interest rate, little exposure in long term investment and less interest on regular tracking expenses. Though the respondents are illiterate, but they had less exposure on financial investment. It shows that most of the women required to take financial training from the organisation with their family, friends, and other welfare associations.